Utilization of Virtual Reality Technology in Knowing the Symptoms of Acrophobia and Nyctophobia - Aisyah Mutia Dawis; Ismail Setiawan (Journal of Applied Science and Technology, 2022)
Acrophobia and Nyctophobia are the most common phobias suffered by people in this world. A phobia is an excessive anxiety or fear of something. Acrophobia is a phobia or fear of being at heights and nyctophobia is an extreme phobia or fear of the night or the dark that can trigger signs of excessive anxiety and hopelessness. This research attempts to know the level phobia a person on child while given exposure virtually. The hypothesis of this research is that there is a significant effect through the use of the new technology, namely virtual reality on changes in physiological responses and different heart rates before and before getting exposure / exposure virtually. The purpose of this research is to investigate a phobia early on in children with the help of vr 3d headset box. The result of this research obtained 4 of 5 children suffering from acrophobia and nyctophobia.